THE EFECTION OF COPERATION CULTURE ON TECHNOLOGY ENGINEER’S LOYALTY IN DIGITAL TRANSFORMTION ERA - Nguyen Thi Thanh Huong (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2023)
Nowadays the terms corporation culture is increasingly used and mentioned as a development criterion of enterprises where many people are gathered with different cultural backgrounds, professional qualifications, awareness levels, social relations, cultural ideology. It is this difference that creates a diverse and complex working environment. In addition to the increasingly fierce competition, enterprises need to maintain stable human resources, minimize leaving the organization of technology engineers, especially good power and talented technology engineers. This is consistent with the current trend when we are in the era of digital transformation, competition based on monetary capital, science and technology, and natural resources is no longer a core competency competition. compete with intellectual capital and human resources. Therefore, it can be said that competing with human resources is very important and an indispensable factor to evaluate the capacity of an organization or enterprise. Code: 23062101